A attapulgite-derived nickel-titanium layered mesoporous catalyst and its preparation method and application

By introducing titanium into the concave and convex rock stone framework, a nickel-titanium layer sheet-shaped mesoporous catalyst was prepared, which solved the problem of inactivation of nickel-based catalysts at high temperatures, achieved efficient biomass tar steam reforming, and produced high hydrogen gas Selective.

CN116422366BActive Publication Date: 2025-02-07ANHUI UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310161228.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-02-07
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

Existing nickel-based catalysts are prone to sintering of carbon deposits and metal nickel particles at high temperatures, resulting in catalyst deactivation and unsatisfactory catalytic capacity.

Method used

By introducing titanium into the concave and concave rock stone framework, a nickel-titanium layer sheet-shaped mesoporous catalyst was prepared, and the low-content nickel was loaded by the impregnation method to improve the resistance to carbon deposits and sintering properties of the catalyst.

Benefits of technology

The catalytic performance and stability of the catalyst are improved, high conversion and high hydrogen yield are achieved, hydrogen selectivity is greater than 70%, and the reaction remains high in 30 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116422366B_ABST
    Figure CN116422366B_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-titanium lamellar mesoporous catalyst derived from attapulgite and its preparation method and application, and the preparation method comprises the following steps: S1, attapulgite is dispersed in a hydrochloric acid solution, and hydrothermal treatment is performed to obtain a attapulgite-based silicon source; S2, the attapulgite-based silicon source and the titanium source are reacted to obtain a reaction mixture containing a Si-O-Ti polymer; S3, a template is added to the reaction mixture, and hydrothermal crystallization is performed to obtain a lamellar mesoporous zeolite carrier derived from attapulgite; S4, nickel is loaded on a carrier by an impregnation method to obtain a nickel-titanium lamellar mesoporous catalyst derived from attapulgite. The catalyst of the present invention is applied to catalyze the steam reforming of biomass tar and its model to prepare hydrogen-rich gas, and a conversion rate greater than 95% can be achieved, a hydrogen yield greater than 65% in synthesis gas, a hydrogen selectivity greater than 70%, and a high activity is still maintained for 30 hours of reaction, with the advantages of green environmental protection, high stability and low price.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a attapulgite-derived nickel-titanium layered flaky mesoporous catalyst and a preparation method and application thereof. Background Art

[0002] Catalytic steam reforming has attracted more and more attention because it can achieve the conversion of tar at low temperature (500-900℃) and produce high-value synthesis gas and hydrogen-rich gas. The most important thing in catalytic steam reforming technology is the catalyst. Among various transition metals, Ni-based catalysts are widely used in catalytic steam reforming because of their low cost, strong ability to break CC bonds and CH, OH bonds, and promote the occurrence of WGS reactions.

[0003] However, since Ni-based catalysts are prone to carbon deposition and sintering of nickel metal particles at high temperatures and thus become inactivated, many researchers have devoted themselves to exploring nickel-based catalysts with improved resistance to carbon deposition and sintering. Different promoters and carriers are one of the solutions to improve the life of catalysts. For example, Yufei Zhao et al reported a metal oxide catalyst with titanium-modified attapulgite (ATP) as a carrier to achieve alkali-resistant NOx catalytic reduction. Through ion exchange, the alkali metal cation impurities in ATP were removed without destroying the initial layered chain structure of ATP to obtain Ti-modified ATP. The octahedral center of Ti and the Si-OH sites rich in modified ATP can anchor alkali metals through coordination bonds or ion exchange without damaging active substances, thereby improving the catalyst's high NOx catalytic reduction ability. However, the catalytic ability of the catalyst is still not ideal, and how to improve the catalytic effect of the catalyst remains to be studied. Summary of the invention

[0004] The main purpose of the present invention is to provide a attapulgite-derived nickel-titanium lamellar mesoporous catalyst with better catalytic performance, and a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides a method for preparing a attapulgite-derived nickel-titanium layered mesoporous catalyst, comprising the following steps:

[0006] S1. Dispersing attapulgite in a hydrochloric acid solution, hydrothermally treating it at a temperature of 150 to 200° C. for 10 to 15 hours, filtering, washing, and drying to obtain a attapulgite-based silicon source;

[0007] S2, adding an attapulgite-based silicon source to ethylene glycol, mixing well, adding a titanium source, and then reacting at a temperature of 100 to 200° C. for 1 to 4 hours to obtain a reaction mixture containing a Si-O-Ti polymer;

[0008] S3, adding a template to the reaction mixture, mixing evenly, and then hydrothermally crystallizing the mixture at 150° C. to 200° C. for 24 to 36 hours, and the obtained product is centrifuged, washed, dried, and calcined to obtain a attapulgite-derived lamellar mesoporous zeolite carrier;

[0009] S4. Loading nickel on the attapulgite-derived lamellar mesoporous zeolite carrier by an impregnation method, followed by drying and calcining to obtain the attapulgite-derived nickel-titanium lamellar mesoporous catalyst.

[0010] Furthermore, in the catalyst, the nickel content is 5 to 20 wt%, and the titanium content is 1.0 to 3.5 wt%.

[0011] Furthermore, in step S1, the concentration of the hydrochloric acid solution is 4 mol / L, and the dosage ratio of attapulgite to the hydrochloric acid solution is 1 g: 5-10 mL.

[0012] Furthermore, in step S2, the titanium source is tetrabutyl titanate, and the usage ratio of attapulgite-based silicon source, tetrabutyl titanate titanium source and ethylene glycol is 2-2.2 g: 0.45-0.5 mL: 10-10.2 mL.

[0013] Furthermore, in step S3, the template is tetrapropylammonium hydroxide, the mass ratio of the template to the attapulgite-based silicon source is 2.5-7.5 g:1-3 g, and the calcination treatment conditions are: air atmosphere, temperature 550° C., and time 6-8 h.

[0014] Furthermore, the nickel precursor salt is nickel nitrate hexahydrate.

[0015] Furthermore, in step S4, the operation process of the impregnation method is: dissolving the nickel precursor salt in a mixture of water and ethanol in a volume ratio of 2 to 3:1, then aging at room temperature for 8 to 12 hours, and then stirring at 60 to 80°C for 5 to 8 hours.

[0016] Furthermore, in step S4, the drying treatment conditions are: temperature 100-120° C., time 8-12 h; the calcination treatment conditions are: air atmosphere, temperature 500-600° C., time 4-6 h.

[0017] The present invention also provides a attapulgite-derived nickel-titanium lamellar mesoporous catalyst, which is prepared according to the above preparation method.

[0018] The present invention also provides the use of the above-mentioned attapulgite-derived nickel-titanium lamellar mesoporous catalyst in the steam reforming of biomass tar and its model product to prepare hydrogen-rich gas.

[0019] The present invention also provides a method for preparing hydrogen-rich gas by steam reforming biomass tar and its model, comprising the following steps: using biomass tar or its model as a reaction raw material, adding the catalyst as claimed in claim 8 to react, and the reaction conditions are: the catalyst dosage is 0.1-0.5g, the water-carbon ratio in the feed is 1:1.5-3, and the weight hourly space velocity is 0.0047-0.008min -1 , reaction temperature 600-800°C; catalyst reduction conditions: treatment at 600-800°C for 1-3h in a 100-150mL / min, 10-15vol% H2 / N2 flow.

[0020] The beneficial effects of the present invention are embodied in:

[0021] The catalyst of the present invention introduces titanium into the attapulgite framework, and the obtained nickel-titanium lamellar zeolite catalyst has a high specific surface area, so that the dispersibility of the metal is enhanced and the catalytic performance is further improved. The catalyst of the present invention uses nickel and titanium as active components, and uses a lamellar mesoporous zeolite carrier derived from attapulgite to load a low content of nickel, so as to achieve relatively high activity. Compared with other nickel-based catalysts, the catalyst of the present invention uses attapulgite as a silicon source, tetrabutyl titanate as a titanium source, and ethylene glycol as a solution to undergo ester exchange polymerization, and then hydrothermally crystallizes in the presence of a template to synthesize a lamellar mesoporous zeolite carrier, and then loads nickel by an impregnation method. The obtained attapulgite-derived nickel-titanium lamellar catalyst has improved the catalyst's ability to resist carbon deposition and sintering.

[0022] The catalyst of the present invention is used in the steam reforming of biomass tar and its model to prepare hydrogen-rich gas, and can achieve a conversion rate of more than 95%, a hydrogen yield in synthesis gas of more than 65%, and a hydrogen selectivity of more than 70%. The catalyst can maintain a relatively high activity after a reaction of 30 hours, has the advantages of being green and environmentally friendly, highly stable, and inexpensive, meets the industrialization requirements of steam reforming of biomass tar and its model to prepare hydrogen-rich gas, can significantly improve the ability of the catalyst to adsorb activated water vapor, and improve the activity of the catalyst, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the carrier prepared in Example 1 of the present invention;

[0024] Figure 2 This is a SEM image of the carrier prepared in Example 1 of the present invention;

[0025] Figure 3 This is a TEM image of catalyst #1 prepared in Example 1 of the present invention;

[0026] Figure 4 This is a TEM image of catalyst #1 prepared in Example 1 of the present invention;

[0027] Figure 5 The N2 adsorption-desorption curve and pore size distribution diagram of the 1# catalyst prepared in Example 1 of the present invention;

[0028] Figure 6 XRD pattern of catalyst #1 prepared in Example 1 of the present invention: N / TS (R): reduced catalyst; N-TS (C): calcined catalyst;

[0029] Figure 7 This is the US-Vis spectrum of catalyst #1 prepared in Example 1 of the present invention: N / TS(R): reduced catalyst; N-TS(C): calcined catalyst; TS: carrier. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, all raw materials used in the following examples are commercially available products known in the art.

[0032] Example 1

[0033] The active component nickel (Ni) content in the attapulgite-derived nickel-titanium lamellar mesoporous catalyst prepared in this embodiment is 5wt% and the titanium (Ti) content is 2.7wt%. The preparation method is as follows:

[0034] S1. Weigh 20 g of mechanically ground attapulgite clay, disperse it in 120 mL of 4 mol / L hydrochloric acid solution to form a suspension I, stir it on a stirring table for 2 h, transfer the suspension I into a 200 mL polytetrafluoroethylene-lined hydrothermal autoclave, hydrothermally treat it at 160 ° C for 10 h, cool it to room temperature and filter it, wash it with deionized water until it is neutral, dry it in an oven at 100 ° C for 10 h, and crush it with a mortar to obtain a attapulgite-based silicon source.

[0035] S2. Put 10 ml of ethylene glycol into a beaker, weigh 2 g of attapulgite-based silicon source and pour it into the beaker, stir on a stirring table until it is evenly mixed, then add 0.5 ml of tetrabutyl titanate, mix evenly, and react at 150° C. for 2.5 hours to complete the polymerization reaction between the silicon source and the titanium source to obtain a reaction mixture containing Si-O-Ti polymer;

[0036] S3, adding 4.6g of tetrapropylammonium hydroxide to the reaction mixture, mixing evenly and transferring into a polytetrafluoroethylene-lined hydrothermal reactor, hydrothermally crystallizing at 180°C for 36h, centrifuging, washing, and drying at 100°C for 10h, heating to 550°C at a heating rate of 4°C / min in an air atmosphere and calcining for 6h, to obtain a attapulgite-derived lamellar mesoporous zeolite carrier;

[0037] S4. Weigh 0.132 g of nickel nitrate hexahydrate and dissolve it in 80 ml of a solution of deionized water and ethanol in a volume ratio of 2:1. Add 0.5 g of the above-mentioned carrier, age it at room temperature for 10 h, stir it on a stirring table at 60°C for 5 h, then put it in an oven at 100°C and dry it for 10 h. Then, heat it to 550°C at a heating rate of 4°C / min in an air atmosphere and calcine it for 4 h to obtain a attapulgite-derived nickel-titanium lamellar mesoporous catalyst, numbered 1#.

[0038] Example 2

[0039] The active component nickel (Ni) content of the attapulgite-derived nickel-titanium lamellar mesoporous catalyst prepared in this embodiment is 10wt% and the titanium (Ti) content is 1.9wt%. The preparation method is as follows:

[0040] S1. Weigh 20 g of mechanically ground attapulgite clay and disperse it in 100 mL of 4 mol / L hydrochloric acid solution to form a suspension I. Stir the suspension on a stirring table for 2 h. Transfer the suspension I into a 200 mL polytetrafluoroethylene-lined hydrothermal autoclave and perform hydrothermal treatment at 170 ° C for 12 h. After cooling to room temperature, filter the mixture, wash it with deionized water until it is neutral, dry it in an oven at 100 ° C for 8 h, and crush it with a mortar to obtain a attapulgite-based silicon source.

[0041] S2, weigh 10.2 ml of ethylene glycol and put it into a beaker, then weigh 2.1 g of attapulgite-based silicon source and pour it into the beaker, put it on a stirring table and stir until it is evenly mixed, then add 0.45 ml of tetrabutyl titanate, mix evenly, and react at 140° C. for 4 hours to complete the polymerization reaction between the silicon source and the titanium source to obtain a reaction mixture containing Si-O-Ti polymer;

[0042] S3. Add 4.8 g of tetrapropylammonium hydroxide to the above reaction mixture, mix well and then transfer into a polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal crystallization at 170°C for 24 hours. The product is centrifuged, washed, and dried at 100°C for 8 hours. Then, the temperature is increased to 550°C at a heating rate of 4°C / min in an air atmosphere and calcined for 6 hours to obtain a attapulgite-derived lamellar mesoporous zeolite carrier.

[0043] S4. Weigh 0.284 g of nickel nitrate hexahydrate and dissolve it in 60 ml of a solution of deionized water and ethanol in a volume ratio of 2:1. Add 0.5 g of the above-mentioned carrier, age it at room temperature for 8 hours, stir it on a stirring table at 70°C for 4.5 hours, then put it in an oven at 100°C to dry it for 8 hours, and then heat it to 500°C at a heating rate of 4°C / min in an air atmosphere and calcine it for 6 hours to obtain a attapulgite-derived nickel-titanium lamellar mesoporous catalyst, numbered 2#.

[0044] Example 3

[0045] The active component nickel (Ni) content in the attapulgite-derived nickel-titanium lamellar mesoporous catalyst prepared in this embodiment is 15wt% and the titanium (Ti) content is 1.7wt%. The preparation method is as follows:

[0046] S1. Weigh 20 g of mechanically ground attapulgite clay and disperse it in 150 mL of 4 mol / L hydrochloric acid solution to form a suspension I. Stir the suspension on a stirring table for 4 h. Transfer the suspension I into a 200 mL polytetrafluoroethylene-lined hydrothermal autoclave and perform hydrothermal treatment at 180 ° C for 10 h. After cooling to room temperature, filter the mixture, wash it with deionized water until it is neutral, dry it in an oven at 110 ° C for 12 h, and crush it with a mortar to obtain a attapulgite-based silicon source.

[0047] S2, weigh 10 ml of ethylene glycol and put it into a beaker, then weigh 2 g of attapulgite-based silicon source and pour it into the beaker, put it on a stirring table and stir until it is evenly mixed, then add 0.48 ml of tetrabutyl titanate, mix evenly, and react at 180° C. for 2 h to complete the polymerization reaction between the silicon source and the titanium source to obtain a reaction mixture containing Si-O-Ti polymer;

[0048] S3. Add 4.8 g of tetrapropylammonium hydroxide to the above reaction mixture, mix well and then transfer into a polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal crystallization at 180°C for 36 hours. The product is centrifuged, washed, and dried at 110°C for 12 hours. Then, the temperature is increased to 550°C at a heating rate of 4°C / min in an air atmosphere and calcined for 8 hours to obtain a attapulgite-derived lamellar mesoporous zeolite carrier.

[0049] S4. Weigh 0.46g of nickel nitrate hexahydrate and dissolve it in a solution of 100ml of deionized water and ethanol in a volume ratio of 2:1. Add 0.5g of the above-mentioned carrier, age it at room temperature for 9h, stir it on a stirring table at 80°C for 4h, then put it in an oven at 110°C and dry it for 12h. Then, heat it to 550°C at a heating rate of 4°C / min in an air atmosphere and calcine it for 5h to obtain a attapulgite-derived nickel-titanium lamellar mesoporous catalyst, numbered 3#.

[0050] Example 4

[0051] The nickel (Ni) content of the active components in the attapulgite-derived nickel-titanium lamellar mesoporous catalyst prepared in this embodiment is 20wt% and the titanium (Ti) content is 1.3wt%. The preparation method is as follows:

[0052] S1. Weigh 20 g of mechanically ground attapulgite clay and disperse it in 200 mL of 3.5 mol / L hydrochloric acid solution to form a suspension I. Stir the suspension on a stirring table for 3 h. Transfer the suspension I into a 200 mL polytetrafluoroethylene-lined hydrothermal autoclave and perform hydrothermal treatment at 180 ° C for 12 h. After cooling to room temperature, filter the mixture, wash it with deionized water until it is neutral, dry it in an oven at 120 ° C for 12 h, and crush it with a mortar to obtain a attapulgite-based silicon source.

[0053] S2, weigh 10.2 ml of ethylene glycol and put it into a beaker, then weigh 2.2 g of attapulgite-based silicon source and pour it into the beaker, put it on a stirring table and stir until it is evenly mixed, then add 0.49 ml of tetrabutyl titanate, mix evenly, and react at 200° C. for 1 hour to complete the polymerization reaction between the silicon source and the titanium source to obtain a reaction mixture containing Si-O-Ti polymer;

[0054] S3. Add 5 g of tetrapropylammonium hydroxide to the reaction mixture, mix well and transfer into a polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal crystallization at 180°C for 36 hours. The product is centrifuged, washed and dried at 120°C for 12 hours, and then heated to 550°C at a heating rate of 4°C / min in an air atmosphere and calcined for 6 hours to obtain a attapulgite-derived lamellar mesoporous zeolite carrier.

[0055] S4. Weigh 0.67g of nickel nitrate hexahydrate, dissolve it in 80ml of a solution of deionized water and ethanol in a volume ratio of 3:1, add 0.5g of the above-mentioned carrier, age it at room temperature for 12h, then stir it on a stirring table at 65°C for 5h, then put it in an oven at 120°C to dry it for 12h, and then heat it to 600°C at a heating rate of 4°C / min in an air atmosphere and calcine it for 4.5h to obtain a attapulgite-derived nickel-titanium lamellar mesoporous catalyst, numbered 4#.

[0056] Example 5

[0057] Structure determination of the catalyst

[0058] The pore size of the catalyst prepared in Example 1 was analyzed by N2 adsorption-desorption test. The results are as follows: Figure 5 And as shown in Table 1.

[0059] Table 1

[0060]

[0061] The above table shows the pore size data of the catalyst. The figure shows that the pore size of the catalyst is about two or three nanometers, which belongs to the mesoporous level. Figure 5 As can be seen from A, the nitrogen adsorption-desorption isotherm of the catalyst is classified as type IV with an H1-type hysteresis loop, indicating that it has a regular pore structure and proving that the catalyst is a regular lamellar mesoporous material with a narrow pore size distribution. Figure 5 This is clearly illustrated by the pore size distribution of N / TS of B.

[0062] See also Figure 6 In the XRD spectrum, at 2θ=24.4°, there is a very complete characteristic peak without splitting, indicating that the titanium species has been successfully introduced into the zeolite framework. Figure 7 The signal generated at 210 nm in the US-Vis spectrum is attributed to the 2p electrons of the bonding oxygen to Ti 4+ The 3d empty orbital transition of the ion and the charge transfer occurred can prove that it contains framework titanium. The shoulder peak at 310nm is attributed to the extra-framework anatase TiO2, and as can be seen in the figure, the peak intensity at 210nm is very large, indicating that most of the titanium enters the lamellar carrier derived from attapulgite.

[0063] Example 6

[0064] Performance test of catalyst for steam reforming of biomass tar and its model products to produce hydrogen-rich gas

[0065] 0.1-0.5 g of the above 1#-4# catalysts were placed in a fixed bed reactor and subjected to reduction treatment at 600-800°C for 2 h in a 100 mL / min, 10 vol% H2 / N2 flow. The performance test was then performed. The feed flow rate was 0.0001 mol / min. The steam supply was obtained by injecting water into the evaporator through a peristaltic pump. The water-to-carbon ratio (S / C) could be changed by adjusting the water injection speed of the pump. The water-to-carbon ratio in the feed was 1:1.5-3, and the weight hourly space velocity was 0.0047-0.008 min -1 Table 2 Performance test of steam reforming of laboratory biomass tar and its model to produce hydrogen-rich gas

[0066]

[0067] From the above results, it can be concluded that the catalyst of the present invention can achieve a feedstock conversion rate of more than 95%, a hydrogen yield of more than 65%, a hydrogen selectivity of more than 70%, and can maintain good stability within 30 hours.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nickel-titanium layered mesoporous catalyst derived from attapulgite, characterized in that: The following steps are involved: S1. Dispersing attapulgite in a hydrochloric acid solution, hydrothermally treating it at a temperature of 150 to 200° C. for 10 to 15 hours, filtering, washing, and drying to obtain a attapulgite-based silicon source; S2, adding an attapulgite-based silicon source to ethylene glycol, mixing well, adding a titanium source, and then reacting at a temperature of 100 to 200° C. for 1 to 4 hours to obtain a reaction mixture containing a Si-O-Ti polymer; The titanium source is tetrabutyl titanate, and the dosage ratio of attapulgite-based silicon source, tetrabutyl titanate titanium source and ethylene glycol is 2-2.2 g: 0.45-0.5 mL: 10-10.2 mL; S3, adding a template to the reaction mixture, mixing evenly, and then hydrothermally crystallizing the mixture at 150° C. to 200° C. for 24 to 36 hours, and the obtained product is centrifuged, washed, dried, and calcined to obtain a attapulgite-derived lamellar mesoporous zeolite carrier; The template is tetrapropylammonium hydroxide, the mass ratio of the template to the attapulgite-based silicon source is 2.5-7.5 g:1-3 g, and the calcination treatment conditions are: air atmosphere, temperature 550° C., and time 6-8 h; S4. Loading nickel on the attapulgite-derived lamellar mesoporous zeolite carrier by an impregnation method, followed by drying and calcining to obtain the attapulgite-derived nickel-titanium lamellar mesoporous catalyst.

2. The method for preparing the attapulgite-derived nickel-titanium layered mesoporous catalyst according to claim 1, characterized in that: In the catalyst, the content of nickel is 5-20wt%, and the content of titanium is 1.0-3.5wt%.

3. The method for preparing the attapulgite-derived nickel-titanium lamellar mesoporous catalyst according to claim 1 or 2, characterized in that: In step S1, the concentration of the hydrochloric acid solution is 4 mol / L, and the dosage ratio of attapulgite to the hydrochloric acid solution is 1 g: 5-10 mL.

4. The method for preparing the attapulgite-derived nickel-titanium lamellar mesoporous catalyst according to claim 1 or 2, characterized in that: In step S4, the operation process of the impregnation method is: dissolving the nickel precursor salt in a mixture of water and ethanol in a volume ratio of 2 to 3:1, then aging at room temperature for 8 to 12 hours, and then stirring at 60 to 80° C. for 5 to 8 hours.

5. The method for preparing the attapulgite-derived nickel-titanium lamellar mesoporous catalyst according to claim 1 or 2, characterized in that: In step S4, the drying treatment conditions are: temperature 100-120° C., time 8-12 h; the calcination treatment conditions are: air atmosphere, temperature 500-600° C., time 4-6 h.

6. A nickel-titanium layered mesoporous catalyst derived from attapulgite, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the attapulgite-derived nickel-titanium lamellar mesoporous catalyst as claimed in claim 6 in the steam reforming of biomass tar and its model product to produce hydrogen-rich gas.

8. A method for preparing hydrogen-rich gas by steam reforming biomass tar and its model products, characterized in that: The following steps are involved: Biomass tar or its model is used as a reaction raw material, and the catalyst as claimed in claim 6 is added to react. The reaction conditions are: the catalyst dosage is 0.1-0.5g, the water-carbon ratio in the feed is 1:1.5-3, and the weight hourly space velocity is 0.0047-0.008min -1 , reaction temperature 600-800°C; catalyst reduction conditions: treatment at 600-800°C for 1-3h in a 100-150mL / min, 10-15vol% H2 / N2 flow.

Citation Information

Patent Citations

  • Hierarchical pore molecular sieve TS-1 and preparation method thereof

    CN111908483A